Optimizing the Spatial Location of Street Lights in Belle Isle, Michigan - Yanqing Xu; Yue Zhang; Cong Fu; Xiyue Deng; Yihe Yang (ISPRS International Journal of Geo-Information, 2022)
Improved street lighting can provide better use of public space and helps to promote safety while driving or walking. In terms of balancing benefits and impacts, on the basis of cost saving, this research adopts two prominent mathematical models, the maximal coverage location problem and the location set covering problem, to optimize street light locations. By comparing with the currently installed lights following the rule of thumb, the mathematical models in this research achieve the effect of saving electric energy while meeting residents’ traffic safety needs and living conditions. Furthermore, the models can provide greater coverage of illumination using the same amount of energy.